Good company [large type] : a novel - Sweeney, Cynthia D'Aprix (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
A warm, incisive new novel about the enduring bonds of marriage and friendship from Cynthia D'Aprix Sweeney, author of the instant New York Times bestseller The Nest. Flora Mancini has been happily married for more than twenty years. But everything she thought she knew about herself, her marriage, and her relationship with her best friend, Margot, is upended when she stumbles upon an envelope containing her husband's wedding ring, the one he claimed he lost one summer when their daughter, Ruby, was five. Flora and Julian struggled for years, scraping together just enough acting work to raise Ruby in Manhattan and keep Julian's small theater company, Good Company, afloat. A move to Los Angeles brought their first real career successes, a chance to breathe easier, and a reunion with Margot, now a bona fide television star. But has their new life been built on lies? What happened that summer all those years ago? And what happens now?